Water scarcity in communities, coping strategies and mitigation measures: the case of Bulawayo - Mukuhlani, Treda; Nyamupingidza, Mandlenkosi (Canadian Center of Science and Education, 2021)
This paper looks at the impact of water scarcity in communities. This paper also evaluates various mitigation measures being employed by residents themselves, local authorities, non-governmental organization (NGOs) and the government. Bulawayo, Zimbabwe’s second largest city was chosen as a case study because the geographical and climatic conditions are such that it receives low and unreliable rainfall. The city has been facing water scarcity for close to a decade now. The water shortages have been recurring over and over again and this has resulted in the Bulawayo City Council introducing water shedding. This has resulted in residents being affected in many ways. Residents’ health has been compromised, sanitation levels have declined and education conditions negatively impacted. The research used purposive sampling. Key informants were interviewed from the City Council, Health department, residents association and NGOs. The research covered three suburbs that are Nketa 7, Entumbane and Newton West. The research found out that the high density suburbs were the most affected by water scarcity and NGO activities were also biased to these areas. Coordinated work between the government, local authority, NGOs and the residents has ensured that a major health crisis be averted.